UMKM Naik Kelas: Pelatihan Digital Marketing untuk Pengrajin Lokal di Desa Sepakek - saruji, Arkan; Said, Manan (Journal of Community Development and Empowerment, 2025)
This community service activity aims to enhance the capacity and competitiveness of Micro, Small, and Medium Enterprises (MSMEs) consisting of local artisans in Sepakek Village through digital marketing training. The development of digital technology offers significant opportunities for MSMEs to expand their markets; however, many business actors in rural areas are still unable to utilize technology optimally. The implementation methods include needs assessment surveys, face-to-face training, practical mentoring, and evaluation of training outcomes. The materials provided cover the creation of digital promotional content, the use of social media for marketing, product photography, and online selling strategies through marketplaces. The training participants consisted of 25 local artisans engaged in bamboo crafts, weaving, and traditional textiles. The results of the activity show a significant increase in participants’ understanding and skills related to digital marketing. A total of 80% of participants successfully created business accounts on social media and independently published their products, while 60% gained new interactions and potential buyers through online platforms. With this training, local artisans are expected to increase their sales turnover, expand market reach, and strengthen the image of local products from Sepakek Village. This program serves as an initial step toward MSME digital independence and the strengthening of the local potential–based economy.